PENGARUH PROMOSI DIGITAL TERHADAP KEPUTUSAN PEMBELIAN SELAMA MASA PANDEMI COVID-19 DI MONERASTORE KABUPATEN GOWA - Andi Tenri Maharani; M. Ikhwan Maulana Haeruddin, Muhammad Ilham Wardhana Haeruddin, Burhannuddin, Zainal Ruma (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The sales promotion strategy carried out in the digital era like today which utilizes social media as a promotional medium is packaged very attractively. The purpose of this research is to analyze the influence of digital promotions on buyer decisions during the Covid-19 pandemic at Monerastore, Gowa Regency. This type of research is quantitative data. The population in this study are Monerastore Consumers in Gowa Regency, 5,542 total Monerastore consumer data in February 2020-February 2021. The Non-probability sample collection technique and Purposive Sampling technique, the sample results in this study totaled 100 respondents. Data were analyzed by simple linear regression using the SPSS program. The results of the study found digital promotion on purchasing decisions for Monerastore in Gowa Regency. It can be concluded that digital promotion has a positive and significant effect on purchasing decisions or influencing purchasing decisions during the Covid 19 pandemic at Monerastore in Gowa Regency